PENGGUNAAN UANG ELEKTRONIK (E-MONEY) SEBAGAI ALTERNATIF PENGGANTI UANG TUNAI MENURUT PERSPEKTIF ISLAM - Meysari, Siti (Kasaba, 2021)
This research aims to determine the attractiveness of using electronic money, knowing the use of electronic money from an Islamic perspective and knowing the contracts used in electronic money transactions. This research uses descriptive qualitative method. Qualitative descriptive method is a data processing method by analyzing the factors associated with the object of research by presenting data in more depth about the object of research. The results of interviews with the three respondents revealed that the attractiveness of electronic money as an alternative to cash is buying and selling activities and transactions that are more efficient, easy, safe and electronic money is currently a trend in society. In Islam, ideal money must be filled with intrinsic and extrinsic elements. But Islam likes the easy. Use of electronic money to facilitate consumers and producers. This means that Islam does not prohibit the use of electronic money as long as its security is guaranteed and the contract used must be in accordance with Islamic law. Electronic money in an Islamic perspective has conditions that do not violate usury, maysir, gharar which we often call prohibited. The contracts used in electronic money are the wadiah contract, qardh contract, shawl contract, murabahah contract, ijarah contract, jualah contract, and wakalah bil ujroh contract. Keywords: The Attractiveness of Electronic Money, Islamic Perspective, Contract